Study on Pore Structure and Fractal Characteristics of Tar-Rich Coal during Pyrolysis by Mercury Intrusion Porosimetry (MIP). (7th October 2022) - Wang, Zhendong; Jiang, Pengfei; Yang, Fu; Kong, Yuanyuan; Ma, Li; Xie, Bohan; Duan, Zhonghui
Abstract : This study aims to show how fractal analysis can be effectively used to characterize the pore structure of porous tar-rich coal. In this study, tar-rich coal pores were obtained by mercury intrusion porosimetry (MIP). The results showed that the sample had a high porosity and large pore diameter after pyrolysis, and the porosity of tar-rich coal was more than 35% at 600°C. The pore-throat ratio at high temperature was large, resulting in the high mercury retention rate. The pore distribution curves of samples at pyrolysis temperatures of 500 and 600°C were unimodal, and those of samples at room temperature and 150, 300, and 400°C were bimodal. The models for calculating fractal dimension based on MIP include Menger sponge model and thermodynamic model. Experiments show that the Menger sponge method is more reasonable when the pore size is less than 50  μ m and greater than 350 nm. For the fractal dimension calculation of the whole pore curve section, the thermodynamic method was more reasonable. The use of fractal analysis in conjunction with the results of classical characterization methods leads to a better understanding of pore evolution in the pyrolysis process of tar-rich coal. The average fractal dimension could also be used as a valid parameter to monitor the textural evolution of the coals.